The costs and outcomes of paediatric tuberculosis treatment at primary healthcare clinics in Johannesburg, South Africa - Budgell, E; Evans, D; Leuner, R; Long, L; Rosen, S (Health and Medical Publishing Group, 2018)
Background. Little up-to-date information is available about the costs of providing drug-susceptible tuberculosis (DS-TB) treatment to paediatric patients in South Africa (SA), nor have actual costs incurred at clinics been compared with costs expected from guidelines. Objectives. To estimate actual and guideline treatment costs by means of a retrospective cohort analysis. Methods. We report patient characteristics, outcomes and treatment costs from a retrospective cohort of paediatric and adolescent (<18 years) DS-TB patients registered for treatment from 1 April 2011 to 31 March 2013 at three primary healthcare clinics in Johannesburg, SA. Actual treatment costs in 2015 SA rands and US dollars were estimated from the provider perspective using a standard bottom-up microcosting approach and compared with an estimate of guideline costs. Results. We enrolled 88 DS-TB patients (median age 4 years (interquartile range 1.0 - 9.5), 44.3% female, 22.7% HIV co-infected, 92.0% pulmonary TB). Treatment success was high (89.8%; 13.6% cured, 76.1% completed treatment), and the mean (standard deviation (SD)) cost per patient with treatment success was ZAR1 820/USD143 (ZAR593/USD46), comprising fixed costs (44.0%), outpatient visits (30.7%), medication (19.3%) and laboratory investigations (6.0%). This was 17% more than the mean (SD) cost estimated by applying treatment guidelines (ZAR1 553/USD122 (ZAR1 620/USD127)), with differences due mainly to higher laboratory costs and more outpatient visits taking place than were recommended in national guidelines. Conclusions. These results are the first reported estimates of paediatric DS-TB treatment costs in SA and show the potential cost savings of closer adherence to national treatment guidelines. The findings were robust in sensitivity analyses and are lower than previous cost estimates in adults.